Finite element dynamic model of multilink flexible manipulators - Beres, Wiesław; Sasiadek, Jerzy Z. (Zielona Góra: Uniwersytet Zielonogórski)
Lagrange's finite element approach is used to formulate the dynamic model of a flexible manipulator system in the three-dimensional space. All manipulator links are considered as slim beams connected in one d.o.f. frictionless revolute joints. Beam-type finite elements, with interpolating polynomials of degree three and six generalized perturbation coordinates per finite element nodal point, are used for description of the link small displacement field.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka